2006
DOI: 10.1111/j.1741-6787.2006.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Base for Practice: Reduction of Restraint and Seclusion Use During Child and Adolescent Psychiatric Inpatient Treatment

Abstract: A B S T R A C TBackground: Restraint and seclusion of children has great potential for harm. Since the mid-1980s, psychiatric inpatient personnel for children and adolescents have put considerable energy in reducing the use of extreme measures of aggression management. While the use of restraints is a particular problem in the United States, aggression management and means of control in psychiatric settings is an international issue.Approach: The core question of this review was: What is the current state of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 99 publications
0
30
0
Order By: Relevance
“…Dean et al considers the interventions a humane and adequate intervention under three conditions [6]: 1) SRU should be part of a global therapeutic approach aimed at behaviour change, with a focus on prevention and use of the least restrictive measures; 2) the time of SRU should be as short as possible, and the patient should have frequent contacts and undergo close monitoring; and 3) SRU should only occur when disruptive and/or dangerous behaviours do not respond to less restrictive interventions, and SRU cannot be executed as punishment or out of indolence. Additionally, SRU has to be transparent, documented and available for internal-and external review in order to avoid abuse [6,7]. In many countries, SRU in minors requires parental consent in most non-urgent situations.…”
Section: Introductionmentioning
confidence: 99%
“…Dean et al considers the interventions a humane and adequate intervention under three conditions [6]: 1) SRU should be part of a global therapeutic approach aimed at behaviour change, with a focus on prevention and use of the least restrictive measures; 2) the time of SRU should be as short as possible, and the patient should have frequent contacts and undergo close monitoring; and 3) SRU should only occur when disruptive and/or dangerous behaviours do not respond to less restrictive interventions, and SRU cannot be executed as punishment or out of indolence. Additionally, SRU has to be transparent, documented and available for internal-and external review in order to avoid abuse [6,7]. In many countries, SRU in minors requires parental consent in most non-urgent situations.…”
Section: Introductionmentioning
confidence: 99%
“…The use of counselling/de-escalation is reflective of the value placed on this method, which is regarded as a core skill of nursing staff in reducing the use of restrictive measures (D'Orio, Purselle, Stevens, & Garlow, 2004). The information on PRN use in the present study is important, given the lack of data in this area and questions regarding its efficacy in managing aggressive and disturbed behaviour (Delaney, 2006). We were not able to explore the overall effectiveness of these strategies in reducing or avoiding the use of restrictive measures, because data were not available on events on the unit where strategies were used successfully in preventing the need for seclusion or restraint.…”
Section: Resultsmentioning
confidence: 98%
“…This could include the introduction of collaborative problem solving, a cognitivebehavioural approach that has been demonstrated to reduce rates of seclusion and restraint in child and adolescent inpatient units (Green, Ablon, & Martin, 2006;Martin et al, 2008). Other approaches identified include discussion with the patient regarding potential triggers and preferences for care during these events, and a focus on trauma-informed care (Delaney, 2006). The potential use of other interventions for aggression, such as time-out, has been advocated (Bowers et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…113 -116 Although consensus is that verbal restraint is preferable to chemical or physical restraint, 117 reviews of the literature find primarily case studies, with a paucity of rigorous studies of verbal restraint, and little on specific strategies or efficacy. 113,118 For example, although a study by Jonikas et al found a decrease in restraint use, it was not clear whether the decrease was attributable to staff training in de-escalation techniques or to crisis intervention training, which occurred at the same time. 119 Other protocols emphasize the importance of prevention in behavior management protocols.…”
Section: Verbal Restraintmentioning
confidence: 95%
“…When treating an agitated patient with a known psychiatric disorder, either a first-or second-generation antipsychotic is generally preferred. Chlorpromazine, a phenothiazine that can be used to treat nausea/vomiting and intractable hiccups, has also been used with agitated patients 118,126,150 but has many of the same adverse effects as the other drugs (extrapyramidal/dystonic symptoms, neuroleptic malignant syndrome) as well as anticholinergic side effects and a decrease in the seizure threshold, without having any major advantages over the other drugs.…”
Section: Drug Selection For Chemical Restraintmentioning
confidence: 99%